Pengaruh Gaji Dan Motivasi Terhadap Kinerja Pegawai Honorer - Syafrizal, Rodi; Sudarjah, Gugum Mukdas (STIE Bina Karya, 2025)
The purpose of this study was to analyze and examine the effect of salary and motivation on the performance of honorary employees of the Environmental Service. The population in this study were all honorary employees of the North Tebing Tinggi City Environmental Service totaling 277 people. The method of determining the number of samples using the slovin formula with a sample of 73 people and determining the sample using incidental techniques. The source of data in this study comes from primary data, namely the results of a questionnaire/questionnaire that is filled in directly by the respondent. Hypothesis testing using multiple regression analysis. The results of this study indicate that partially salary has a positive and significant effect on employee performance, but partially motivation does not significantly affect employee performance. While simultaneously variable salary and motivation have a positive and significant effect on the performance of honorary employees.